Pelatihan Pengolahan dan Diversifikasi Produk Aren untuk Pemberdayaan UMKM Desa Sukaharja Kabupaten Tasikmalaya - Cepi Rahmat Hidayat; Riga Zahara Nurani; Intan Rahayu; Hidayah Dwiyanti; Triana Setyawardani; Ardiansyah Ardiansyah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance the capacity and skills of Silih Asih MSME actors in Sukaharja Village, Tasikmalaya Regency, in producing premium-quality palm sugar products and developing value-added product innovations. The program was implemented through training and mentoring activities involving 20 participants. Evaluation instruments included written tests (pre-test and post-test), skill observation sheets, and participant response questionnaires. Data were analyzed using descriptive quantitative methods by comparing participants’ average pre-test and post-test scores to assess overall competency improvement. The results indicate a significant increase in participants’ competencies, with the average pre-test score improving from 58 to 88 in the post-test. In addition to enhanced technical skills, participants also gained a better understanding of the importance of quality standards and attractive packaging design. These findings demonstrate that the program is effective in fostering self-reliance and enhancing the competitiveness of MSMEs based on local potential.